A cyto-epidemiological study on married women in reproductive age group (15-49 years) regarding reproductive tract infection in a rural community of West Bengal - Shamima Yasmin; Anindya Mukherjee (Wolters Kluwer Medknow Publications, 2012)
Background: Reproductive tract infection (RTI) represents a major public health problem in India. Women are either not aware of the symptoms of RTI or refuse to seek health care due to economic and time constrains unless suffering from alarming symptoms. Objectives: To find out the prevalence of women with suggestive symptoms of RTI; to identify clinical and cytological abnormalities among the symptomatic women and to find out association between socio-demographic profile and risk factors with RTI symptomatic and cytology positive patients. Materials and Methods: A total of 385 married women in reproductive age group residing in Baligori sub-center area in Tarakeswar block of Hooghly district, West Bengal, India, were screened for symptom suggestive of RTI; symptomatic women went through gynecological examination and cancer cervix screening by Pap smear. Analysis of results was done by Odds ratio and multivariate logistic regression. Results: Overall, 23.6% of the study population had symptoms suggestive of RTI. Most of them (68.1%) had abnormal vaginal discharge. Among the symptomatic women, cytology proved that 24.4% were suffering from acute cervicitis, 4.7% from A Squamous Cell of Undetermined Significance (ASCUS) and 2.3% from Low Grade Intra epithelial Lesion (LSIL) Squamous. Statistically significant association was observed for age, number of children, contact history of husband, pond bathing, menstrual hygiene, intra uterine device insertion, non-usage of barrier method, and history of abortion among women symptomatic for RTI and asymptomatic women. Conclusions: Prevalence of suggestive symptoms of RTI in women was found to be high (23.6%), and among them 7% had cervical dysplasia. Therefore, enhancing awareness and organizing screening camps are absolute necessity and must be held at frequent intervals to curb the menace due to cervical cancer.